(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Ovarian dysfunction is a complex functional disorder driven by interactions among neuroendocrine, immune, metabolic, and genetic factors. This review article presents contemporary concepts of the pathogenetic mechanisms underlying ovarian dysfunction, emphasizing the role of cytokines, disturbances in hypothalamic-pituitary-ovarian axis regulation, and immune and genetic determinants. Special attention is given to diagnostic approaches and interdisciplinary aspects of patient management. The review is based on the analysis of recent data from authoritative international sources.